La retraduction, ou l’historicité des traductions : un élan francophone ? - Enrico Monti (Romanica Wratislaviensia)
Our paper aims to revisit retranslation studies through a few key figures from the French-speaking world. Interestingly enough, almost all the major figures in francophone translation studies have dealt with this topic. Berman opened the way by seeing retranslation as a space for translation’s fulfilment. Meschonnic proclaimed: “as much as I can, I retranslate”. Ballard identified it as one of the constant elements in the history of translation, while Gambier was the first to outline a map of retranslation studies. In the 2010s, retranslation has become a major research topic in translation studies, and francophone translation studies have been a driving force behind it.